Work and union movement in the new brazilian car industry centers - Ribeiro, Rosana; Cunha, Sebastião (FCL-UNESP Laboratório Editorial, 2007)
Motor industry in Brazil has increased in the 90s, when companies set up plants outside of São Paulo in search for workers with no experience in trade union negotiations, among others motives. In this article we focus on the cases of Mitsubishi in Catalão (state of Goiás) and Volkswagen in Resende (Rio de Janeiro), by analyzing the organization of work, workers’ socioeconomic profiles and union movement in these plants. Although working conditions at MMC are seen as outmoded, both plants maintain a hybrid organization. A good deal of workers comes from Catalão and includes young highly educated males lacking, however, the industrial culture peculiar to the automotive sector as well as tradition in union trading. The lack of labor union tradition, however, starts to erode. In Resende the union seems to be committed to the workers it represents: it takes part in collective bargaining and keeps a factory committee. In Catalão a labor union was created in late 2004 and began to fight for the interests of its base.